Integrating hierarchical and network centric management approaches in construction megaprojects using a holonic methodology. Issue 3 (6th August 2020) - Gorod, Alex; Hallo, Leonie; Statsenko, Larissa; Nguyen, Tiep; Chileshe, Nicholas
Abstract : Purpose: Traditional "hierarchical" and "network-centric management" approaches often associated with the management of well-defined construction projects lack the adaptability to cope with uncertainty, standardised practices and the required conformance to industry standards. The purpose of this paper is to propose an integrative "holonic" methodology for the management of megaprojects in the construction industry, which incorporates both adaptability and conformance to standards, and to illustrate the associated benefits of such a methodology. Design/methodology/approach: A multi-case study comprising three cases delivered in the USA and Australia, namely the Adelaide Desalination Plant (ADP), the Seattle–Tacoma International Airport, and the Olmsted Locks and Dam Replacement project were utilized to demonstrate the key features of the hierarchical, network-centric and holonic approaches to managing megaprojects. Findings: The case studies demonstrate incorporating the holonic approach into the management of complex construction projects results in increased management effectiveness and project success. The proposed "holonic" methodology provides the potential to efficiently manage megaprojects navigating through high degrees of uncertainty. Practical implications: The adoption of the holonic view by project management (PM) practitioners will help them manage megaprojects that are characterised by greater complexity. Second, the proposed methodology enables the discipline of PM to evolve in alignment with rapidly unfolding global transformation trends. Originality/value: This paper demonstrates the application of the "holonic" methodology to the domain of the management of construction megaprojects. Such an approach is needed as construction projects become increasingly more complex across the world due to technological, political and social uncertainties, larger scale, changing environmental and safety regulations, and the growing involvement of human factors germane to this research.